2006
DOI: 10.1017/s0031182006001740
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A1fromTrypanosoma cruziinfective stages generates lipid messengers that activate host cell protein kinase c

Abstract: Here we have studied phospholipase A1 (Plase A1) from Trypanosoma cruzi infective stages and it's possible role regarding the interaction with mammalian host cells. Plase A1 was mainly detected as a membrane-bound activity in the infective amastigote and trypomastigote stages, being remarkably higher with respect to the non-infective epimastigotes. It is noteworthy that only the infective stages secreted Plase A1. Moreover, along the differentiation process from epimastigotes into metacyclic trypomastigotes, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 38 publications
0
34
0
1
Order By: Relevance
“…cruzi [34] and also the pro-kineticin receptors in mammalian cells, which are G protein-coupled receptors [35]. Moreover, it has been described an activation of host protein kinase C by RA strain (TcVI) that favors infection [36]. In this study, we found that T .…”
Section: Discussionmentioning
confidence: 55%
“…cruzi [34] and also the pro-kineticin receptors in mammalian cells, which are G protein-coupled receptors [35]. Moreover, it has been described an activation of host protein kinase C by RA strain (TcVI) that favors infection [36]. In this study, we found that T .…”
Section: Discussionmentioning
confidence: 55%
“…However, since we could only identify sn -1 C18:0-, C18:1-, and C18:2-LPC, we believe that the parasite PLA1 is not playing a major role in the generation of these LPCs, at least under the experimental conditions used in this study. Nevertheless, we could not discard the possibility that the T. cruzi PLA1 might be important for the generation of LPC species using different experimental conditions and/or other parasite strains, as previously described [79], [80]. Therefore, most likely the LPC species identified in this study were generated by the action of a PLA2 from the host and/or parasite.…”
Section: Discussionmentioning
confidence: 77%
“…These LPCs could be generated by the action of host- and/or parasite-derived phospholipase(s) A1 and/or A2 on diacyl-PCs. A PLA1 has already been well characterized in T. cruzi trypomastigote and amastigote forms (RA, Cvd, and K98 strains) [79], [80] and T. brucei [81]. However, since we could only identify sn -1 C18:0-, C18:1-, and C18:2-LPC, we believe that the parasite PLA1 is not playing a major role in the generation of these LPCs, at least under the experimental conditions used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Disrupted parasites were then centrifuged at 27,000×g for 30 min and the resultant homogenate supernatants were aliquoted and stored at −80°C until used in immunoblot analysis of PKC isoenzymes (Belaunzarán et al 2007). …”
Section: Measurement Of Intracellular Calcium Concentration In Oa-stimentioning
confidence: 99%